A model for hepatic fibrosis: the competing effects of cell loss and iron on shortened modified Look‐Locker inversion recovery T1 (shMOLLI‐T1) in the liver. Issue 2 (23rd July 2016) - Tunnicliffe, Elizabeth M.; Banerjee, Rajarshi; Pavlides, Michael; Neubauer, Stefan; Robson, Matthew D.
Abstract : Purpose: To propose a simple multicompartment model of the liver and use Bloch‐McConnell simulations to demonstrate the effects of iron and fibrosis on shortened‐MOLLI (shMOLLI) T 1 measurements. Liver T 1 values have shown sensitivity to inflammation and fibrosis, but are also affected by hepatic iron content. Modified Look‐Locker inversion recovery (MOLLI) T 1 measurements are biased by the lower T 2 associated with high iron. Materials and Methods: A tissue model was generated consisting of liver cells and extracellular fluid (ECF), with iron‐dependent relaxation rates. Fibrosis was imitated by increasing the ECF proportion. Simulations of the shMOLLI sequence produced a look‐up table (LUT) of shMOLLI‐ T 1 for a given ECF fraction and iron content. The LUT was used to calculate ECF(shMOLLI‐ T 1 ), assuming normal hepatic iron content (HIC), and ECF(shMOLLI‐ T 1, T 2 * ), accounting for HIC determined by T 2 *, for 77 patients and compared to fibrosis assessed by liver biopsy. Results: Simulations showed that increasing HIC decreases shMOLLI‐ T 1, with an increase in HIC from 1.0 to 2.5 mg/g at normal ECF fraction decreasing shMOLLI‐ T 1 by 160 msec, while increasing ECF increased ShMOLLI‐ T 1, with an increase of 20% ECF at normal iron increasing shMOLLI‐ T 1 by 200 msec. Calculated patient ECF(shMOLLI‐ T 1 ) showed a strong dependence on Ishak score (3.3 ± 0.8 %ECF/Ishak stage) and 1 / T 2 * (–0.23 ± 0.04 %ECF/Hz). However, when iron was accounted for to produce ECF(shMOLLI‐ T 1, T 2 * ), it was independent of HIC but retained sensitivity to Ishak score. Conclusion: Use of this multicompartment model of the liver with Bloch‐McConnell simulation should enable compensation of iron effects when using shMOLLI‐ T 1 to assess fibrosis. Level of Evidence: 1 J. Magn. Reson. Imaging 2017;45:450–462.